Analisis Gaya Bahasa dan Makna pada Lirik Lagu Penyemangat Anti-Epidemi (抗疫公益歌曲) - Nadya Padma Sari Aulia; Tri Budianingsih; Feri Ansori (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
This study examines the language style and intertextual meaning contained in 5 anti-epidemic song lyrics that were selected based on the amount of people's interest. The anti-epidemic song is a song that was released specifically as a form of support and to show empathy for the difficult situation that is currently happening due to the infectious disease known as COVID-19. This study looks at how musicians communicate through song lyrics to convey a sense of empathy and spirit to the community, as well as see whether there is a relationship between song lyrics and texts or social and historical conditions in society. The method used in this study is a descriptive qualitative method, the results of this study are the language styles that are found to be very diverse, namely: 借代 (jièdài), 反语 (fǎnyǔ), 婉曲 (wǎnqū), 对偶 (duì'ǒu), 比喻 (bǐyù), 反复(fǎnfù), 对比 (duìbǐ), 映衬 (yìngchèn), 排比 (páibǐ), 顶真 (dǐngzhēn), 夸张 (kuāzhāng), 双关 (shuāngguān) and 比拟 (bǐnǐ), it can be strung together into amazing song lyrics and managed to give a certain effect for those who listen, the meaning is also very closely related to the real conditions that are happening in the community so that these songs can be received very well. Keywords – Language Style, Intertextual Study, Anti-Epidemic Song